SISTEM PEMERINTAHAN INDONESIA DAN IMPLIKASINYA DALAM KEHIDUPAN BERBANGSA DAN BERNEGARA - Sukadi, Imam (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractIn principle the system of government that refers to the form of the relationship between the legislative with the executive branch. system of government comes from the combination of two words and governance systems. system of government is a system of relations between the executive organ and legislative organs. The purpose of state government are generally based on the ideal or goal state. The purpose of state government to protect the whole nation Indonesia is Indonesia and to promote the general welfare, the intellectual life of the nation, as well as participate in the establishment of world order based on freedom, abiding peace and social justice. The institutions are in a system of government in Indonesia to work together and support each other for the realization of the purpose of governance in Indonesia.Keywords: governance; Indonesia; systemsAbstrakPada prinsipnya sistem pemerintahan itu mengacu pada bentuk hubungan antara lembaga legislatif dengan lembaga eksekutif. sistem pemerintahan berasal dari gabungan dua kata system dan pemerintahan. sistem pemerintahan adalah sistem hubungan antara organ eksekutif dan organ legislatif. Tujuan pemerintahan negara pada umumnya didasarkan pada cita-cita atau tujuan negara. Tujuan pemerintahan negara Indonesia adalah melindungi segenap bangsa Indonesia dan untuk memajukan kesejahteraan umum, mencerdaskan kehidupan bangsa, serta ikut melaksanakan ketertiban dunia yang berdasarkan kemerdekaan, perdamaian abadi dan keadilan social. Lembaga-lembaga yang berada dalam satu sistem pemerintahan Indonesia bekerja secara bersama dan saling menunjang untuk terwujudnya tujuan dari pemerintahan di negara Indonesia.